Glutathione Transferase Omega-1 Regulates NLRP3 Inflammasome Activation through NEK7 Deglutathionylation - Mills, Kingston; Corr, Sinead; Palsson Mcdermott, Eva; Mc Gettrick-Dillon, Anne (My University, 2019)
NLRP3 inflammasome activation contributes to chronic inflammationassociated with autoinflammatorydisease, yet understanding of NLRP3inflammasome regulation is incomplete.Hughes et al. show that thedeglutathionylating enzyme GSTO1-1promotes NLRP3 inflammasomeactivation through deglutathionylation ofNEK7. Furthermore, the GSTO1-1inhibitor C1-27 reduces NLRP3inflammasome activationin vitroandin vivo.
PUBLISHED
cited By 0
Keywords: NLRP3 inflammasome activation; GSTO1-1 glutathione; NEK7; IL-1β; Deglutathionylation; Pyroptosis; Immunology, Inflammation & Infection